Analysis of Mental and Physical Workload on Kerupuk Sehati - Ina Siti Hasanah; Alfian Ardi Nugroho (Engineering Faculty, UNSOED, 2024)
The Kerupuk Sehati Factory produces and sells cooked and raw crackers. The production capacity of raw crackers is 1000 kg per day for 8-9 working hours with 17 employees. The problem is that workers feel an excessive physical workload, so worker performance decreases and workers cause errors, namely, products become defective. This research aims to measure workers' mental and physical workload and make improvements so that workers' workload is reduced. Workers' mental workload was measured using the NASA-TLX method, and workers' physical workload was measured using the CVL method. Measurement results based on NASA-TLX revealed that the average mental workload is in the high category of eleven workers and the very high category of six workers. The calculated CVL values showed that the two greatest physical workloads were felt by Respondent A, with a CVL value of 31.36%, and Respondent L, with a CVL value of 38.93%. Reducing physical and mental workload is recommended by adding exhaust fans, checking machines and equipment before production, using conveyance, organizing training, and providing rest areas.